USING MODERN METHODS OF PROTECTING ECONOMIC INFORMATION - Doston Imomaliyev (The Conference Hub, 2025)
Economic information is one of the most valuable assets in the modern digital economy, necessitating advanced security measures to protect it from cyber threats, unauthorized access, and data breaches. The emergence of sophisticated cyberattacks, including phishing, ransomware, and insider threats, requires organizations to adopt modern methods for securing economic data. This paper examines various contemporary techniques used to safeguard economic information, including encryption, blockchain, artificial intelligence (AI)-driven security mechanisms, multi-factor authentication, and intrusion detection systems. The study highlights the importance of a multi-layered security approach and emphasizes the role of regulatory compliance and best practices in data protection.
Keywords: Economic information security, encryption, blockchain, artificial intelligence, multi-factor authentication, cybersecurity, regulatory compliance, intrusion detection.